A limitation to determine heat transfer of water at supercritical pressure: The repeatability issue. (25th January 2023) - Ferrand, Thomas; Oettig, Jan; Schäfer, Laura; Gschnaidtner, Tobias; Naja, Mohamad Omar; Wieland, Christoph; Spliethoff, Hartmut
Highlights: Published data indicates non-reproducibility of the heat transfer in the pseudo-critical region. Non-reproducibility appears at conditions for which DHT is possible. Experimental results at the Technical University of Munich confirm this hypothesis. Origin of the non-reproducibility may be linked to variations of the properties close to the pseudo-critical points. Abstract: As the heat transfer is based on physical processes which are expected to be deterministic, a major anticipation is that the experimental data should show good repeatability, if not reproducibility. In other words, it is expected that repetition of experiments with very similar inputs (bulk pressure and enthalpy, mass flow rate, heat flux …), should result in consistent and very similar outputs (heat transfer coefficient or inside wall temperature). However, comparable experiments with supercritical water in the literature, although rather scarce, as well as the experimental work conducted at the Chair of Energy Systems at the Technical University of Munich tend to show that repeatable or reproducible data are difficult to obtain. This is the case particularly within the pseudo-critical region where DHT is likely to occur. This may impair the ability to assess accurately the overheating of the piping in critical cases, and therefore the safety of the concerned plants. This paper aims to focus on this problem from an experimental perspective, trying to identify both the magnitude of the phenomenon as well as at which parameters non-reproducibility occurs. Ultimately, the authors try to answer the following question: Is it possible to reach reproducibility?